2021
DOI: 10.1093/mnras/stab1244
|View full text |Cite
|
Sign up to set email alerts
|

AstroSat observation of the HBL 1ES 1959+650 during its October 2017 flaring

Abstract: We present the results of the X-ray flaring activity of 1ES 1959+650 during October 25-26, 2017 using AstroSat observations. The source was variable in the X-ray. We investigated the evolution of the X-ray spectral properties of the source by dividing the total observation period (∼130 ksecs) into time segments of 5 ksecs, and fitting the SXT and LAXPC spectra for each segment. Synchrotron emission of a broken power-law particle density model provided a better fit than the log-parabola one. The X-ray flux and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…"Orphan" flares hint at a more complex geometry and/or underlying particle distribution, such as those invoked in multiple-component SSC models and/or external Compton models (e.g., the synchrotron mirror model, Böttcher & Dermer (1999)) within the leptonic schemes. Recently, Shah et al (2021), have reported an anti-correlation between the photon index and X-ray flux using a broken power-law for analysing only a segment of X-ray data presented here.…”
Section: Introductionmentioning
confidence: 77%
“…"Orphan" flares hint at a more complex geometry and/or underlying particle distribution, such as those invoked in multiple-component SSC models and/or external Compton models (e.g., the synchrotron mirror model, Böttcher & Dermer (1999)) within the leptonic schemes. Recently, Shah et al (2021), have reported an anti-correlation between the photon index and X-ray flux using a broken power-law for analysing only a segment of X-ray data presented here.…”
Section: Introductionmentioning
confidence: 77%
“…On the other hand, variations in the acceleration or diffusion time-scales would lead to changes in the distribution shape, which in turn would lead to rather dramatic changes in the density of particles at energies >> γ0. In the simple picture, where the distribution is a power-law, changes in the index would lead to large variations in the value of the distribution at large γ since the power-law would be approximately "pegged" at the pivot point γ0 (Shah et al 2021). This is generically true and one would expect large variations in the inferred normalization at some large γ with spectral shape variations, which is not observed.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…Note that this is not exactly the same as having a one-time injection of particles into the system and studying their evolution but to solve the corresponding time-dependent equation with some physical parameter varying continuously with time. In a recent work Shah et al (2021) have shown that such a model may indeed solve the generic problem of large spectral shape variation with modest changes in the normalization.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, during a MW campaign of 1ES 1959+650 between April 29 and November 21 of 2016, the MAGIC telescopes observed multi-TeV flaring events for the nights of 13th, 14th of June and 1st of July 2016 when the position of the synchrotron peak was in the EHBL range, and again, exhibiting extreme HBL-like behavior (MAGIC Collaboration et al 2020b). Several other authors have also studied the MW SED of 1ES 1959+650 (Shah et al 2021;Chandra et al 2021).…”
Section: Introductionmentioning
confidence: 99%